Fabrication of Curcumin@Ag Loaded Core/Shell Nanofiber Membrane and its Synergistic Antibacterial Properties - Wang, Qiuxiang; Liu, Songlin; Lu, Wenjuan; Zhang, Pingping (Frontiers in Chemistry, 2022)
The core/shell structure nanofiber membrane loaded with curcumin and silver nanoparticles was prepared by coaxial electrospinning technology, which is a high-efficiency combined antibacterial material composed of photodynamic antibacterial agent and metal nanoparticle. As a photosensitizer, curcumin could generate singlet oxygen under laser irradiation. Silver nanoparticles have antibacterial properties, and could also enhance the singlet oxygen production of curcumin due to the metal-enhanced singlet oxygen effect, thereby producing a synergistic antibacterial effect. Compared with the antibacterial rate of uniaxial curcumin fiber membrane (45.65%) and uniaxial silver nanoparticle-loaded fiber membrane (66.96%), the antibacterial rate of curcumin@Ag core/shell structure fiber membrane against Staphylococcus aureus is as high as 93.04%. In addition, the antibacterial experiments show that the core/shell fiber membrane also has excellent antibacterial effects on Escherichia coli.